A companion to Vittoria Colonna - Brundin, Abigail; Crivelli, T.; Sapegno, Maria Serena (Renaissance society of America texts & studies series ;, 2016)
Vittoria Colonna (1490-1547) was the genre-defining secular woman writer of Renaissance Italy, whose literary model helped to establish a decorous and wholly assimilated voice for women within the field of Italian literature. The book brings together an international and interdisciplinary group of leading scholars to assess Colonna's contribution, both as a writer, a role model, and a contributor to important religious debates of the era. This book, while amply fulfilling the remit of providing a useful and comprehensive handbook to meet the needs of students and scholars at earlier and advanced levels, aims in addition to do more than this, by drawing into a single volume for the first time scholarship from across disciplines in which Vittoria Colonna's influence has been felt, including literary criticism, religious history, history of art and music.